1997
DOI: 10.1126/science.278.5345.1947
|View full text |Cite
|
Sign up to set email alerts
|

Mediation of Sonic Hedgehog-Induced Expression of COUP-TFII by a Protein Phosphatase

Abstract: A Sonic hedgehog (Shh) response element was identified in the chicken ovalbumin upstream promoter-transcription factor II (COUP-TFII) promoter that binds to a factor distinct from Gli, a gene known to mediate Shh signaling. Although this binding activity is specifically stimulated by Shh-N (amino-terminal signaling domain), it can also be unmasked with protein phosphatase treatment in the mouse cell line P19, and induction by Shh-N can be blocked by phosphatase inhibitors. Thus, Shh-N signaling may result in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
79
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 141 publications
(84 citation statements)
references
References 21 publications
5
79
0
Order By: Relevance
“…Motor neurons (presumably at all axial levels) are induced normally in mouse Gli1, Gli2, and Gli3 single knockouts (Ding et al, 1998;Matise et al, 1998;Park et al, 2000), and in Gli1:Gli2 and Gli1:Gli3 double mutants (Ding et al, 1998;Park et al, 2000). These data suggest that, in mouse, Shh signaling may induce motor neurons indirectly by suppressing Gli repressor function or that Gli-independent pathways may be involved (Krishnan et al, 1997). Consistent with the former, motor neurons are induced in the ventral neural tube of Shh:Gli3 double mutants, indicating that Shh signaling antagonizes the function of Gli3 in repressing motor neuron induction (Litingtung and Chiang, 2000b).…”
Section: Induction Of Branchiomotor Neuronssupporting
confidence: 57%
“…Motor neurons (presumably at all axial levels) are induced normally in mouse Gli1, Gli2, and Gli3 single knockouts (Ding et al, 1998;Matise et al, 1998;Park et al, 2000), and in Gli1:Gli2 and Gli1:Gli3 double mutants (Ding et al, 1998;Park et al, 2000). These data suggest that, in mouse, Shh signaling may induce motor neurons indirectly by suppressing Gli repressor function or that Gli-independent pathways may be involved (Krishnan et al, 1997). Consistent with the former, motor neurons are induced in the ventral neural tube of Shh:Gli3 double mutants, indicating that Shh signaling antagonizes the function of Gli3 in repressing motor neuron induction (Litingtung and Chiang, 2000b).…”
Section: Induction Of Branchiomotor Neuronssupporting
confidence: 57%
“…Unlike COUP-TFI, COUP-TFII is highly expressed only in the anterior half of the cerebellum in a manner similar to that of Sonic hedgehog (Shh), which is important for cerebellar foliation (Corrales et al, 2004(Corrales et al, , 2006. Since COUP-TFII is more likely to be a downstream target of Shh signaling (Krishnan et al, 1997;Takamoto et al, 2005), it is reasonable to expect that COUP-TFII may play an important role in cerebellar development. Additionally, when one considers the temporal expression pattern of COUP-TFI and ERR␥, it is probable that they may also function during cerebellar development.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have suggested that the Hh pathway is bifurcated and that the Hh signal can be transduced independently of Ci (Krishnan et al, 1997;Lessing and Nusse, 1998;Lewis et al, 1999;Suzuki and Saigo, 2000;Gallet et al, 2000). The existence of this distal branch point has been disputed (Méthot and Basler, 2001).…”
Section: Emc Controls the Pace Of Furrow Movement Through Regulation mentioning
confidence: 99%